Anxiety- and depression-like behavior in mice lacking the CD157/BST1 gene, a risk factor for Parkinson's disease - Lopatina, Olga; Yoshihara, Toru; Nishimura, Tomoko; Zhong, Jing; Akther, Shirin; Fakhrul, Azam A. K. M.; Liang, Mingkun; Higashida, Chiharu; Sumi, Kohei; Furuhara, Kazumi; Inahata, Yuki; Huang, Jian-Jung; et al. (Frontiers in Behavioral Neuroscience, 2014)
CD157, known as bone marrow stromal cell antigen-1, is a glycosylphosphatidylinositol-anchored ADP-ribosyl cyclase that supports the survival and function of B-lymphocytes and hematopoietic or intestinal stem cells. Although CD157/Bst1 is a risk locus in Parkinson’s disease (PD), little is known about the function of CD157 in the nervous system and contribution to PD progression. Here, we show that no apparent motor dysfunction was observed in young knockout (CD157-/-) male mice under less aging-related effects on behaviors. CD157-/- mice exhibited anxiety-related and depression-like behaviors compared with wild-type mice. These behaviors were rescued through treatment with anti-psychiatric drugs and oxytocin. CD157 was weakly expressed in the amygdala and c-Fos immunoreactivity was less evident in CD157-/- mice than in wild-type mice. These results demonstrate for the first time that CD157 plays a role as a neuro-regulator and suggest a potential role in pre-motor symptoms in PD.